Financial Literacy Teaching Module Based on Social Inquiry Model in Elementary School Social Studies - Darmayanti, Mela; Khairunnisa, Aghni (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the importance of financial literacy. Financial literacy is one of the essential literacy of 21st-century skills that every individual in the world must master. Financial literacy needs to be taught to Elementary School (SD) students by integrating it into existing subjects. However, financial literacy education in Indonesia is rare, and elementary schools still need teaching modules to support financial literacy. The integration of financial literacy in elementary schools can positively impact students. The survey results prove that not all Indonesian people are well-literate. This research aims to develop financial literacy teaching module for elementary school students using the social inquiry learning model. This research used the Design and Development method with the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 4th-grade elementary school students, learning experts, learning media experts and 4th-grade teachers. Data collection techniques were carried out by filling out work logs and through expert validation. The data analysis technique used is qualitative and quantitative analysis. The teaching module is organized into seven sections: the concept of money (earning money concept), economic activities, budgeting, spending, saving, sharing, and business idea development exercises. The results of the study were the teaching module get validation ratings in the very good category. N-Gain is used to test the effectiveness and the results showed to be effective in the high category. It was concluded that this financial literacy teaching module based on social inquiry can improve the learning outcomes of elementary school students.